EVALUATION OF PHARMACEUTICAL STORAGE BASED ON PHARMACEUTICAL SERVICE STANDARDS AND IMPROVEMENT STRATEGIES USING SWOT METHOD AND ISLAMIC SHARIA AT PROF. DR. SOEROJO MENTAL HOSPITAL MAGELANG - Rahma Sari, Dila; Rosyid, Abdur; Maretasari, Fajar Dewi (SAINS INDONESIANA, 2025)
Storage is a critical process within the pharmaceutical logistics distribution system, involving the placement and maintenance of pharmaceutical preparations and Medical Consumable Materials (BMHP) in designated areas to protect them from theft, physical damage, and environmental factors that may reduce product quality. From an Islamic perspective, medicine storage should not be conducted carelessly, considering that some pharmaceutical ingredients may not be halal and lack halal certification. To minimize the risk of contamination or mixing during storage, proper categorization and labeling based on halal status are essential. This research employed a descriptive methodwith both qualitative and quantitative approaches. Primary data were collected through checklists administered to pharmacy staff and direct observation of the drug storage area. The compliance level of the pharmaceutical logistics storage room at RSJ Soerojo Magelang with the Technical Guidelines for Hospital Pharmaceutical Services (2019)was found to be 80.70% for spatial layout and 81.82% for storage system aspects. However, from the Islamic sharia perspective, the storage system does not meet the requirements, as indicated by a 0% score for halal-based drug classification and labeling. SWOT analysis places RSJ Soerojo in Quadrant I (aggressive strategy), with an IFAS score of 1.26 and an EFAS score of 0.29, indicating strong internal strengths and external opportunities, allowing the hospital to actively pursue strategic development.